Effect Of Resistance Spot Welding Parameters On Copper And Brass - Saad, Nurihal Hanim Mat (2012)

(untitled)
Resistance spot welding is the most commonly used method for joining sheet metals. Most studies in this technique were focus on selected materials and little information is available regarding the response and behaviour of copper and copper alloy. Thus, in this research is purposed to study the effect of resistance spot welding parameters on copper and brass alloy. The copper and brass welded by resistance spot welding technique under varied welding currents and applied loads has been investigated. A nugget measurement looked at the influence of loads (60 N, 65 N, 70 N and 75 N) and weld currents (5.50 kA, 6.00 kA and 6.50 kA) on both fusion area and internal porosity.